2020
DOI: 10.4103/ijd.ijd_822_19
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide, multicentric case–Control study on vitiligo (MEDEC-V) to elicit the magnitude and correlates

Abstract: Background: Vitiligo is an acquired, idiopathic, and common depigmentation disorder. The values of various epidemiologic parameters are often doubtful due to the methodological weaknesses of the studies. Aims: To elicit the magnitude of various epidemiological parameters and important correlates of vitiligo. Materials and Methods: Every vitiligo patient attending the outpatient department of medical colleges spread over most of the Indian sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Depression and anxiety were the most commonly reported psychosocial comorbidities. Forty-one studies reported depression or depressive disorders (including major depressive disorder, bipolar disorder, and dysthymic disorder) in patients with vitiligo, with a prevalence range from 0.1–62.3% [ 15 , 17 , 22 , 23 , 28 , 30 , 32 , 34 , 35 , 39 , 40 , 43 , 44 , 46 , 48 , 50 , 57 , 68 , 69 , 71 , 92 , 100 , 104 , 113 115 , 131 , 137 , 138 , 142 , 143 , 145 , 146 , 150 , 154 , 155 , 158 160 , 163 , 177 ]. Twenty studies reported anxiety or anxiety-related disorders (including generalized anxiety disorder, agoraphobia, social phobia [not social avoidance], and panic disorder), with a prevalence of 1.9–67.9% [ 22 , 23 , 30 , 34 , 39 , 43 , 44 , 46 , 50 , 57 , 92 , 115 , 137 , 138 , 150 , 154 , 155 , 158 , 159 , 175 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Depression and anxiety were the most commonly reported psychosocial comorbidities. Forty-one studies reported depression or depressive disorders (including major depressive disorder, bipolar disorder, and dysthymic disorder) in patients with vitiligo, with a prevalence range from 0.1–62.3% [ 15 , 17 , 22 , 23 , 28 , 30 , 32 , 34 , 35 , 39 , 40 , 43 , 44 , 46 , 48 , 50 , 57 , 68 , 69 , 71 , 92 , 100 , 104 , 113 115 , 131 , 137 , 138 , 142 , 143 , 145 , 146 , 150 , 154 , 155 , 158 160 , 163 , 177 ]. Twenty studies reported anxiety or anxiety-related disorders (including generalized anxiety disorder, agoraphobia, social phobia [not social avoidance], and panic disorder), with a prevalence of 1.9–67.9% [ 22 , 23 , 30 , 34 , 39 , 43 , 44 , 46 , 50 , 57 , 92 , 115 , 137 , 138 , 150 , 154 , 155 , 158 , 159 , 175 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with controls, psychosocial comorbidities noted to be significantly ( p ≤ 0.05) associated with vitiligo were depression (11 studies) [ 23 , 28 , 33 , 34 , 55 , 63 , 128 , 140 , 143 , 145 , 155 ], anxiety (ten studies) [ 23 , 30 , 33 , 34 , 55 , 63 , 119 , 128 , 140 , 155 ], emotional or behavioral impairment (six studies) [ 9 , 23 , 34 , 128 , 140 , 161 ], adjustment disorder (four studies) [ 15 , 30 , 37 , 128 ], low self-esteem (three studies) [ 57 , 65 , 134 ], relationship and sexual dysfunction (three studies) [ 33 , 155 , 161 ], sleep disturbance (two studies) [ 55 , 117 ], suicidality (one study) [ 128 ], self-consciousness (one study) [ 119 ], embarrassment (one study) [ 145 ], alexithymia (one study) [ 108 ], and alcohol abuse or addiction (one study) [ 128 ]. Five studies reported that depression [ 30 , 84 , 85 , 102 , 164 ] and/or anxiety [ 84 , 164 ] scores measured by Beck Inventory scales were not significantly different in patients with vitiligo vs controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations